Screening, verification, and analysis of biomarkers for drug-induced cardiac toxicity in vitro based on RTCA coupled with PCR Array technology. (15th February 2017) - Zhang, Lu; Xu, Meng-Xi; Yin, Qing-Sheng; Zhu, Cai-Ying; Cheng, Xue-Lian; Ren, Yi-Ran; Zhuang, Peng-Wei; Zhang, Yan-Jun
Highlights: A high-throughput assessment of drug-induced cardiotoxicity in vitro. The common predictive genomics biomarkers of Rps6kb1 was identified and verified in several drugs. Ingenuity Pathway Analysis (IPA) was applied to combine relevant pathways of RPS6KB1 in human species. Abstract: Cardiotoxicity is one of the most serious side effects of new drugs. Early detection of the drug induced cardiotoxicity based on the biomarkers provides an important preventative strategy for detecting potential cardiotoxicity of candidate drugs. In this study, we aim to identify the predictive genomics biomarkers for drug-induced cardiac toxicity based on the RTCA coupled with PCR Array technology in primary cells. Three prototypical cardiotoxic compounds (doxorubicin, isoproterenol, ouabain) with different mechanisms were firstly real-time monitored to diagnose the cytotoxicity by using the RTCA, while the functional alterations of cardiomyocytes were also monitored by analyzing the beating frequency of cardiomyocytes. Then cardiac specific toxicity gene expression changes were studied by using the technology of PCR Array, which can detect the changes of 84 cardiac functions related genes. Rps6kb1 was identified to be the common cardiac biomarkers by using multivariate statistical and integration analyses. The biomarker was further verified by selecting other drugs with or without cardiotoxicity, and the results showed that the gene exhibited specific changes in cardiac toxicity. Moreover, IPA was applied to combine relevant pathways of Rps6kb1, and identify the main types of cardiac toxicity. These results would further enrich the evaluating strategy of drug-induced cardiotoxicity in vitro, and Rps6kb1 could be used as the specific biomarker of cardiotoxcity during safety assessment of the novel drug candidates.